Need for New Benchmark Replacing Natural Gas as Energy Cost/Price Base - Kendall, Kevin (Clean Energy Technologies, 2025)
Since Wind and Solar renewable energy costs dropped below Natural Gas (NG) prices in 2017, there has been an increasing problem setting the price for electrical energy, which this century has been based on NG because cheaper coal has declined in usage to cut carbon emissions. The background is that renewable Wind and Solar are now more economic than NG, and are increasing rapidly in application, yet calculations of energy prices are still regularly based on NG cost. For example, electricity prices today relate more to NG than to renewables although more than 50% of UK electricity now comes from Wind and other renewables in 2025. The key problem is that Wind and Solar outputs fluctuate considerably and cannot be compared directly with electricity from an NG power station which delivers continuously. Consequently, energy storage mechanisms must be added to renewable power if fair comparisons are to be made. Lithium battery and Hydrogen gas storage are plausible options. This paper compares Wind/Solar plus Lithium battery electric storage with Wind/Solar and Hydrogen gas energy stores as replacements for NG to create a new benchmark. The conclusion is that this new benchmark should be deϐined before 2030 when most of UK grid electricity is planned to be green.